(untitled) (El-Wahat Journal for Research and Studies, 2020)
This study aims to show the interest of Al Baraka Bank of Algeria and the Islamic Bank of Jordan in social responsibility, and to measure their commitment to their social role.The study concluded that there is a contribution from the Islamic banks studied in spending on social responsibility programs in varying proportions, and that these banks do not pay much attention to the disclosure of their social identity.In light of the results of the study, we recommend that Al Baraka Bank of Algeria should work to increase the spending on social responsibility programs, as well as the need to evaluate the disclosure of both banks about their social role through annual reports. Key words- Social responsibility , Islamic banks, Al Baraka Bank of Algeria, Jordan Islamic Bank, Social identity index.